Cyclometalated platinum(II) complexes containing monodentate phosphines: antiproliferative study - Samouei, Hamidreza; Rashidi, Mehdi; Heinemann, Frank Wilhelm (Journal of the Iranian Chemical Society, 2014)
Reaction of cyclometalated platinum(II) precursor [Pt(C boolean AND N)Cl(dmso)], 1, C boolean AND N = N(1), C(2')-chelated deprotonated 2-phenylpyridine and dmso = dimethylsulfoxide, with 1 equivalent of triphenyl phosphine, PPh3, or 1,3,5-triaza-7-phosphaadamantane, PTA, gave the complex [Pt(C boolean AND N)Cl(PPh3)], 2, or [Pt(C boolean AND N)Cl(PTA)], 3, respectively. On the basis of careful multinuclear NMR spectroscopy, supported by a number of 2D NMR experiments, structures of the complexes 2 and 3 in solution were determined to be neutral four coordinate. The X-ray crystallography indicated that the solid-state structure of complex 3 comprised a common square-planar geometry around platinum(II). Cytotoxicity of the complexes 2 and 3 was studied in three human cancer cell lines derived from ovarian carcinoma (CH1), lung carcinoma (A549), and colon carcinoma (SW480).
Keywords: Cyclometalated complex; Phosphine; Antitumor study; Platinum; NMR